Financial Technology with QRIS Payment System for Entrepreneurship Locker - Victorio Almers Chrisetya Putra; FX Hendra Prasetya; Bernardinus Harnadi; Albertus Dwiyoga Widiantoro (SISFORMA, 2023)
The Covid-19 pandemic has an impact not only on health but also on human activities, one of which is economic transactions.  A number of policies related to health protocols have caused limitations for the community in transacting with each other. In relation to economic transactions, entrepreneurial transactions on campus have stopped due to policies related to the pandemic. To answer this problem, an invention called "Culinary Business Automatic Service Locker (Entrepreneurship Locker)" that based on the Internet of Things that implements financial technology in its payment method was created. The implementation of Financial Technology is intended to revive entrepreneurship on campus by providing a “new user experience” to all parties involved in these activities. In recent years, financial technology as a new concept in payments has been growing. The concept of finance technology is to create a payment platform where there is no longer a need for physical interaction between the seller and the buyer, because the transaction process occurs via digital. QRIS, which stands for Quick Response Code Indonesia Standard is one of the financial technology-based payment methods that has been authorized in Indonesia. There are two types of QRIS, namely static QRIS and dynamic QRIS. In this study, the dynamic QRIS API will be used because it is able to generate different nominal and QR codes for different transaction. In addition, an e-wallet is needed for users to support payments by scanning the QR code via smartphone. This research wants to see how the application of financial technology using dynamic QRIS and e-wallet to entrepreneurial lockers. The results showed that financial technology using dynamic QRIS and e-wallets can be utilized in the automatic payment system for entrepreneurial lockers